An inversion-free method for finding positive definite solution of a rational matrix equation - Soleymani, Fazlollah; Sharifi, Mahdi; Vanani, Solat Karimi; Haghani, Farhad Khaksar; Kilicman, Adem (Hindawi Publishing Corporation, 2014)
A new iterative scheme has been constructed for finding minimal solution of a rational matrix equation of the form X + A * X-1 A = I. The new method is inversion-free per computing step. The convergence of the method has been studied and tested via numerical experiments.